Growing up in transit. Personal development and resistance of migrant adolescents travelling through Mexico unaccompanied - Susanna Corona Maioli; Delan Devakumar; Shoshana Berenzon Gorn; Rochelle A. Burgess (Journal of Migration and Health)
Mexico is a major global migration corridor. The last decade has seen an increase in adolescents travelling unaccompanied from Guatemala, Honduras and El Salvador, mainly due to violence and natural disasters. This group of migrants is exposed to migration risks such as trafficking and exploitation, as well as multiple deportations and long waiting times without appropriate access to health and education services. These conditions have significant documented adverse impacts on health and mental health, but the impact on personal development has been less explored. Thus, this article aims to explore the impact of migration transit on identity and resilience of unaccompanied migrant youth, psychosocial mental health constructs that are important for wellbeing and personal development. Through 47 semi-structured interviews conducted with migrant youth and different migration workers in summer 2021 in two migrant shelters in Mexico City and Guadalajara, we found that possibilities for identity building for migrant youth were restricted in a context of curbed freedom. Violence and poverty led to loss of crucial formative years, pushing many to aspire only to work – regardless of the type of work. Resilience overlapped with resistance but was generally maintained with cultural narratives of goal achievement, faith and hope. Strong responsibility towards sending remittances to family made family one of the main goals of the migration journey. Workers highlighted how regional migration management, underlined by discriminatory policies which place profit and national security ideology before a recognition of common humanity, is a considerable barrier to funding services and advancing access to rights for youth. However, youth showed recognition of their own agency and humanity, which represents an important basis on which to build a counter-discriminatory vision and management of this migration. Results are reported according to COREQ guidelines.